The Influence of Empowerment Leadership on The Proactive Behavior of Employees in The Department of Women's Empowerment, Protection Children and Communities of Binjai City - Khaerunisa, Kherunisa; Sugiarto, Abdi (PT. Multidisciplinary Press Indonesia, 2024)
The aim of this research is to determine and analyze the influence of empowerment leadership on proactive behavior in the Women's Empowerment, Child Protection and Community Services of Binjai City. This research was conducted using a causal associative quantitative approach. The sample used was all employees with a total of 61 people taken using proportional sampling. The research results show that empowering leadership has a positive and significant effect on proactive behavior. This is shown by the T-count value of T-count of 1.978 > t table 1.67109, with a significance value of 0.053 < 0.05. The regression coefficient shows that if empowerment leadership is increased by 1 unit, proactive behavior will increase by 0.059 units assuming other variables remain constant. Apart from that, the results of the determination test show an Adjusted R Square value of 0.046 or 4.60%, which indicates that empowerment leadership has a very low influence on proactive behavior, while the remaining 95.40% is influenced by other factors that have not been studied. Thus, partially, empowering leadership has a positive but not significant effect on proactive behavior in the Women's Empowerment, Child Protection and Community Service of Binjai City. This identifies that improvements in empowering leadership can contribute to increased proactive behavior.